The Implementation of the PLITA Habituation Program in Shaping the Religious Character of Students at SDN 2 Giriwangi - Via Nurafiati Astuti; Dasim Budimansyah; Asep Dahliyana; Kama Abdul Hakam; Imas Kurniawaty; Abih Gumelar (Dinasti International Journal of Education Management and Social Science, 2025)
The decline in students’ moral and spiritual values highlights the urgency of developing character education based on religious habituation. This study was motivated by the need to instill Islamic character values in elementary school students through meaningful and consistent routines. The purpose of this research is to describe the implementation and effectiveness of the Program Literasi Agama Islam (PLITA) or Islamic Religious Literacy Program at SDN 2 Giriwangi in shaping the religious character of fifth- and sixth-grade students. The PLITA program is conducted every Thursday through a series of activities, including the recitation of Asmaul Husna, reading short Qur’anic surahs, chanting Sholawat Nabi, short religious lectures, interactive discussions, and structured reflective assignments. This study employed a qualitative descriptive approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and documentation of PLITA activities. The data were analyzed using the Miles and Huberman interactive model data reduction, presentation, and conclusion drawing—with triangulation for validation. The results show that PLITA significantly contributes to improving students’ religious attitudes, discipline, responsibility, and spiritual awareness. Students became more engaged, polite, and active in religious practices, while teachers played a crucial role as role models and value reinforcers. The findings align with the theories of Habituation (Skinner), Social Learning (Bandura), and Character Education (Lickona), emphasising repetition, modelling, and internalisation of values. In conclusion, PLITA is an effective and innovative religious education model based on habituation and reflective literacy, fostering religious character and discipline among elementary students.